The preclinical phase of the pathological process underlying sporadic Alzheimer’s disease - Braak, Heiko; Del Tredici, Kelly (Brain (London, England : 1878), 2015)
Abnormal tau lesions (non-argyrophilic pretangle material, argyrophilic neuropil threads, neurofibrillary tangles) in select types of neurons are crucial for the pathogenesis of sporadic Alzheimer's disease. Ongoing formation of these tau lesions persists into end-stage Alzheimer's disease and is not subject to remission. The early pretangle disease phase is a focus of increasing interest because only abnormal forms of the microtubule-associated protein tau are involved at that point and, in contrast to late-stage disease when amyloid-β deposition is present, this phase is temporally closer to the prevailing conditions that induce the pathological process underlying Alzheimer's disease. Extracellular and aggregated amyloid-β may only be produced under pathological conditions by nerve cells that contain abnormal tau. One potential trigger for tau protein hyperphosphorylation and conformational change in Alzheimer's disease may be the presence of a non-endogenous pathogen. Subsequently, a predictable regional distribution pattern of the tau lesions develops in phylogenetically late-appearing and ontogenetically late-maturing neurons that are connected via their axons. It is hoped that hypotheses drawn from these considerations, as well as from recent tau dissemination models, from studies of variant tau conformers, and from tau imaging will encourage the development of new preventative and disease-modifying strategies.